<

Exercice

Montrer que , pour tout r é el x , sin x + cos x 2 = 1 + 2 sin x cos x

Pour tout r é el x : sin x + cos x 2 = sin 2 x + 2 sin x cos x + cos 2 x ( a ) ( a ) Pour tout r é el x : cos 2 x + sin 2 x = 1 = 1 + 2 sin x cos x

sin 4 x + cos 4 x + 2 sin 2 x cos 2 x = 1

Pour tout r é el x : sin 4 x + cos 4 x + 2 sin 2 x cos 2 x = sin 2 x 2 + 2 sin 2 x cos 2 x + cos 2 x 2 ( a ) ( a ) Pour tous r é els a et b : ( a + b ) 2 = a 2 + 2 ab + b 2 = sin 2 x + cos 2 x 2 ( b ) ( b ) Pour tout r é el x , cos 2 x + sin 2 x = 1 = 1

cos 4 x sin 4 x + 2 sin 2 x = 1

Pour tout r é el x : cos 4 x sin 4 x + 2 sin 2 x = cos 2 x 2 sin 2 x 2 + 2 sin 2 x ( a ) ( a ) Pour tous r é els a et b : a 2 b 2 = ( a + b )( a b ) = cos 2 x + sin 2 x cos 2 x sin 2 x + 2 sin 2 x ( b ) ( b ) Pour tout r é el x : cos 2 x + sin 2 x = 1 = cos 2 x sin 2 x + 2 sin 2 x = cos 2 x + sin 2 x ( b ) = 1

sin 6 x + cos 6 x 2 sin 4 x cos 4 x + sin 2 x = 0

On constate que l ' on peut s é parer les termes en sin x de ceux en cos x : sin 6 x + cos 6 x 2 sin 4 x cos 4 x + sin 2 x = sin 6 x 2 sin 4 x + sin 2 x + cos 6 x cos 4 x = sin 2 x sin 4 x 2 sin 2 x + 1 + cos 4 x cos 2 x 1 = sin 2 x sin 2 x 2 2 sin 2 x + 1 + cos 4 x cos 2 x 1 ( a ) + ( b ) ( a ) Pour tous r é els a et b : ( a b ) 2 = a 2 2 ab + b 2 ( b ) Pour tout r é el x : cos 2 x + sin 2 x = 1 cos 2 x 1 = sin 2 x = sin 2 x sin 2 x 1 2 cos 4 x sin 2 x ( c ) ( c ) Pour tout r é el x : cos 2 x + sin 2 x = 1 sin 2 x 1 = cos 2 x = sin 2 x × cos 2 x 2 cos 4 x sin 2 x = sin 2 x cos 4 x sin 2 x cos 4 x = 0